Variation in the Use of Vestibular Diagnostic Testing for Patients Presenting to Otolaryngology Clinics with Dizziness. (1st July 2016) - Piker, Erin G.; Schulz, Kris; Parham, Kourosh; Vambutas, Andrea; Witsell, David; Tucci, Debara; Shin, Jennifer J.; Pynnonen, Melissa A.; Nguyen‐Huynh, Anh; Crowson, Matthew; Ryan, Sheila E.; Langman, Alan; et al.
Abstract : Objective: We used a national otolaryngology practice–based research network database to characterize the utilization of vestibular function testing in patients diagnosed with dizziness and/or a vestibular disorder. Study Design: Database review. Setting: The Creating Healthcare Excellence through Education and Research (CHEER) practice‐based research network of academic and community providers Subjects and Methods: Dizzy patients in the CHEER retrospective database were identified through ICD‐9 codes; vestibular testing procedures were identified with CPT codes. Demographics and procedures per patient were tabulated. Analysis included number and type of vestibular tests ordered, stratified by individual clinic and by practice type (community vs academic). Chi‐square tests were performed to assess if the percentage of patients receiving testing was statistically significant across clinics. A logistic regression model was used to examine the association between receipt of testing and being tested on initial visit. Results: A total of 12, 468 patients diagnosed with dizziness and/or a vestibular disorder were identified from 7 community and 5 academic CHEER network clinics across the country. One‐fifth of these patients had at least 1 vestibular function test. The percentage of patients tested varied widely by site, from 3% to 72%; academic clinics were twice as likely to test. Initial visit vestibular testing also varied, from 0% to 96% of dizzy patients, and was 15 times more likely in academic clinics. Conclusion: There is significant variation in use and timing of vestibular diagnostic testing across otolaryngology clinics. The CHEER network research database does not contain outcome data. These results illustrate the critical need for research that examines outcomes as related to vestibular testing.